Design of modern schools under construction in the Republic of Uzbekistan in accordance with international architectural standards. (Journal of Pedagogical Inventions and Practices, 2022)
It is known that after the independence of Uzbekistan, a lot of attention was paid to education, especially general secondary education. In particular, in order to improve the quality of secondary education, large-scale schools have been built for many conveniences, and music and art schools for gifted students. The article discusses how well the designed schools have been built over the years.